Insulin secretory status and insulin indices after 5 years of index pregnancy with gestational diabetes mellitus - Islam, Md. Hasanul; Airi, Krishna; Tofail, Tania; Hasanat, Muhammad Abul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Women with a previous history of Gestational Diabetes Mellitus (GDM) have a higher risk of developing adverse metabolic outcomes in comparison to women without GDM. Although after delivery dysglycemia usually subsides, insulin resistance and β-cell defects may not disappear completely postpartum, eventually leading to type-2 diabetes mellitus. So, it is meaningful to investigate the long-term changes in insulin secretion and resistance after delivery. Aim: The aim of this study is to assess the insulin resistance and insulin secretory status of mothers with a history of GDM ≥ 5 years of index pregnancy. Method: In this hospital-based cross-sectional study,107 women with a history of GDM and 101 women without GDM participated. Fasting insulin and C-peptide were measured by the chemiluminescence method. Homeostatic Model Assessment (HOMA) was used to estimate β-cell secretory function (HOMA-B), insulin resistance (HOMA-IR), and insulin sensitivity (HOMA-%S). Data were analyzed by SPSS (version 25). Results: Median time elapsed after index pregnancy was 9 years for the GDM group and 7 years for the NGT group (p=0.004). C-peptide was significantly higher in the GDM group compared to the NGT group [3 (2.34-3.74) vs. 2.52(2.16-3.35); p=0.011]. Fasting insulin and HOMA-IR had similar trends [15.3 (10.6-19.2) vs. 13.3 (10.0-17.25); p=0.044 and 4.06 (2.71-6.25) vs. 3.11 (2.25-4.34); p<0.001, respectively]. On the other hand, HOMA-B was lower among GDM compared to the NGT [117.13 (74.39-185.28) vs. 159.45 (121.91-206.43); p<0.001]. Fasting insulin level (p<0.001), C-peptide (p<0.001), and HOMA-IR (p<0.001) increased progressively with the change of current glycemic status across the NGT, prediabetes (PDM), and diabetes (DM) groups. There was a gradual decline in β-cell function from the NGT to the DM group based on the current glycemic status (p<0.001). Conclusion: Women with GDM also had substantial β-cell dysfunction and insulin resistance after ≥ 5 years of index pregnancy. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S43]